The Emergence of Tool Use in Preterm Infants - Petkovic, Maja; Rat-Fischer, Lauriane; Fagard, Jacqueline (Frontiers in Psychology, 2016)
Preterm born children without neurological impairments have been shown to present some visual-manual coordination deficits, more or less depending on their tonicity and the degree of prematurity. In this paper, we compare the development of tool use in 15-23-month-old preterm infants born after 33-36 weeks of gestation without neurological complications with that of full-term infants according to corrected age. Understanding the affordance of a tool is an important cognitive milestone in early sensorimotor period. Using a tool to bring within reach an out-of-reach object, for instance, has been shown to develop during the second year in full-term infants. Here we presented preterm infants with an attractive toy out of reach and with a rake-like tool within reach in five conditions of spatial relationships between the toy and the tool. Like full-terms, preterm infants used the tool with success in conditions of spatial contiguity around 15-17 months. In conditions of a spatial gap between tool and toy, i.e. the only conditions which shows without ambiguity that the infant understands the affordance of the tool, preterm infants as a group showed no delay for tool use: the frequency of spontaneous successes started to increase after 18 months, and demonstration became effective after that age. However, further analyses showed that only the preterm infants without hypotonia and born after 36 weeks of pregnancy developed tool use without delay. Hypotonic preterm infants were still largely unsuccessful in the conditions of spatial gap, even at the end of the study. The degree of prematurity also influenced the performance at tool use. These results, following the observation of a delay in the development of bimanual coordination and of handedness in the same infants at 10-12 months in a previous study, show that low risk preterm infants can still be impaired for the development of new manual skills beyond the first year. Thus, hypotonic preterm infants and infants born before 36 weeks of pregnancy should be followed and might benefit from early intervention programs.